Acceptance of e-learning using artificial intelligence technology in military education process in UAE - Ali Alnaqbi, Ali Mohamed (2022)
Recently, UAE has adopted Artificial Intelligence (AI) and e-learning systems in several fields, including education. Military colleges have embraced this new technology with the institutions running on the conventional educational system. This study assessed the current adoption status, challenges, and strategies of using an AI-based e-learning system in the UAE military-based colleges. This study aims to identify the level of acceptance of e-learning using artificial intelligence (AI) technology in the military education process in the UAE from students and teachers of the Joint Command and Staff College (JCSC). It is a quantitative assessment study based on students' and teachers' perceptions of UAE-JCSC. Data was collected using a questionnaire survey, where the questionnaire was distributed to a total of 240 JCSC students and teachers at the college. However, only 207 completed forms were received. The questions were divided into three sections: level of adoption, challenges, and strategies in using an AI-based e-learning education system. It was concluded there are statistically positive significant relationships between the three factors: the current AI and e-learning application; strategies and budgets set by the state to implement AI and e-learning; the availability of critical success factors in applying AI and e-learning in military colleges process and the improvement of flow at the significance level P=0.000 < 0.05. However, challenges encountered by AI and eLearning applications in the military education process are strongly but negatively correlated with the acceptance of AI in Military colleges. Those four variables explain 98.5% of the variation and change in the acceptance of AI and e-learning in military colleges. The findings from this study are beneficial; it provides a valuable source of information for devising strategies to promote the uses of these modern tools and motivate the students to get the maximum benefits of AI and e-learning technologies. It is expected that this study will have several contributions and positive repercussions that can be summarized in theoretical and practical assistance. It constitutes a helpful reference for future studies if it provides for subsequent researchers and scientists interested in artificial intelligence valuable literature and recommendations related to critical success factors in the application of artificial intelligence and e-learning in military colleges. This study will have practical implications for students in encouraging them to use AI and e-learning techniques to improve access to resources and new learning methods and motivate decision-makers in the UAE. To provide intelligent applications for teaching the military students to enable them to receive education and maintain their military training simultaneously.